The Productivity Puzzle – A Critical Assessment and an Outlook on the COVID-19 Crisis - Felix Roth (University of Hamburg, Chair of International Economics, 2021)
This paper assesses the productivity puzzle critically and gives an outlook on the COVID-19 crisis. It offers two main conclusions. First, it posits that a large fraction of the productivity puzzle can be solved by incorporating intangible capital into the asset boundary of the national accounts. Thus, the productivity puzzle is largely explained as a consequence of fundamental structural changes that are underway, transforming industrial economies into knowledge economies. Secondly, the contribution foresees a post-COVID-19 scenario that will likely lead to a pronounced increase in labour productivity growth. This depends, however, on whether the current push for digitization will be backed by actual investments into digitization and the necessary complementary investments in (business and public) intangible capital.
Keywords: E22; F45; O32; O34; O47; O52; 330; productivity puzzle; intangible capital; labour productivity growth; structural change; COVID-19 crisis; re-measurement of GDP